2011
DOI: 10.1111/j.1399-3046.2011.01502.x
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C and neutrophil gelatinase‐associated lipocalin as markers of renal function in pediatric heart transplant recipients

Abstract: We hypothesized that use of Schwartz formula underestimates the prevalence of CKD in PHT recipients. This study determined the prevalence and risk factors for CKD in PHT using novel methods-serum cystatin C, CKiD formula, Revised Schwartz formula, s- and u-NGAL. Serum BUN, creatinine, cystatin C and s- and u-NGAL were measured after prospective enrollment. Schwartz formula GFR was compared with novel methods. CKD was defined as CKiD GFR < 90 mL/min/1.73 m(2) . The s- and u-NGAL were compared between those with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 32 publications
1
21
0
1
Order By: Relevance
“…In current clinical practice, AKI is diagnosed by measuring Cre and/or blood urea nitrogen levels, but these markers are insensitive and late indicators of AKI [2]. Previous studies demonstrated that uNGAL levels for AKI were increased within 2 h, and a diagnosis using Cre levels was delayed by 1 to 3 days [3,4], which may be consistent with our case.…”
Section: To the Editorsupporting
confidence: 88%
“…In current clinical practice, AKI is diagnosed by measuring Cre and/or blood urea nitrogen levels, but these markers are insensitive and late indicators of AKI [2]. Previous studies demonstrated that uNGAL levels for AKI were increased within 2 h, and a diagnosis using Cre levels was delayed by 1 to 3 days [3,4], which may be consistent with our case.…”
Section: To the Editorsupporting
confidence: 88%
“…After heart and lung transplantation, plasma NGAL was also not correlated with cystatin C and estimated GFR [35]. Finally, only urine NGAL was found to be correlated with CKD in type 2 diabetics with nephropathy and in pediatric heart transplant recipients [36,37]. These literature data indicate the need for a study involving CKD patients at various functional stages with stable renal function, to evaluate the relationship of plasma and urine concentrations of NGAL with measured GFR.…”
Section: Discussionmentioning
confidence: 99%
“…In current clinical practice, AKI is typically diagnosed by measuring blood urea nitrogen (BUN) and serum creatinine (SCr), but it is well recognized that BUN and SCr are insensitive and late indicators of AKI. 10 More recently, urine neutrophil gelatinase-associated lipocalin (uNGAL) has been considered more sensitive and specific test to detect AKI. 11 However, uNGAL is also a marker of systemic inflammation since it is typically released by neutrophils upon activation.…”
Section: Introductionmentioning
confidence: 99%